Denkbeelde oor God by Hosea - Boshoff, W. S. (Verbum et ecclesia, 1997)
Conceptions of God in Hosea The book Hosea could be characterised as a polemic against particular traits of Israelite religion. According to the book’s message Yahweh was deeply involved in Israel's everyday existence. His involvement is presented in terms of three critically important aspects of His being as the only God: He is God of history, God of nature and He is the High God. The basic premise that Yahweh was the God of Israel’s past is common ground between Hosea and his contemporaries, but the prophet’s message is that Yahweh also governs the present and future. The Israelites are moreover accused that they depend on the ‘baalim’ for their natural and agricultural needs. Now Yahweh is proclaimed as the God in command of every aspect of nature and fertility. Although He is a High God, Yahweh is not remote, but close by. He does make a difference and He is very relevant to Israel’s everyday existence.